Rate of loading, but not lower limb kinematics or muscle activity, is moderated by limb and aerial variation when surfers land aerials - Forsyth, J. R.; Richards, C. J.; Tsai, M.-C.; Whitting, J. W.; Riddiford-Harland, D. L.; Sheppard, J. M.; Steele, J. R. (Journal of Sports Sciences, 2021)
We aimed to determine whether there were any differences in how surfers used their lead and trail limbs when landing two variations of a simulated aerial manoeuvre, and whether technique affected the forces generated at landing. Fifteen competitive surfers (age 20.3 ± 5.6 years, height 178.2 ± 9.16 cm, mass 71.0 ± 10.5 kg) performed a Frontside Air (FA) and Frontside Air Reverse (FAR), while we collected the impact forces, ankle and knee muscle activity, and kinematic data. A principal component analysis (PCA) was used to reduce 41 dependent variables into 10 components. A two-way MANOVA revealed that although there were no limb x aerial variation interactions, surfers generated significantly higher relative loading rates at landing for the trail limb compared to the lead limb (+28.8 BW/s; F(1,303) = 20.660, p < 0.0001, n² = 0.064). This was likely due to the surfers "slapping" the trail limb down when landing, rather than controlling placement of the limb. Similarly, higher relative loading rates were generated when landing the FA compared to the FAR (+23.6 BW/s; F(1,303) = 31.655, p < 0.0001, n² = 0.095), due to less time over which the forces could be dissipated. No relationships between aerial variation or limb were found for any of the kinematic or muscle activity data. Practitioners should consider the higher relative loading rates generated by a surfer`s trail limb and when surfers perform a FA when designing dry-land training to improve the aerial performance of surfing athletes.